Enhancing Water Resource Protection: A Data-Driven Approach to Reuse and Recycling in Green Buildings - Ramezanianpour, Mohammad; Singh, Parambir (2024 4th International Conference on Smart City and Green Energy (ICSCGE), 2024)
New Zealand has one of the highest average daily freshwater consumption rates among developed nations. Small rural communities in New Zealand face significant challenges in securing a reliable and safe water supply, often experiencing water scarcity during peak summer periods and compromised water quality during flooding events. This research introduces a novel, data-driven approach to a water reuse scheme for a small rural community in the Taranaki region, integrating rainwater harvesting, greywater, and blackwater management across five houses and one school. The project integrates rainwater harvesting, greywater, and blackwater management, adhering to New Zealand's water treatment standards and Code of Practice. Environmental monitoring tools were employed to track key parameters such as water quality, usage patterns, and system efficiency. Utilizing EPANET software, the study simulates the water reuse system over daily, weekly, and yearly periods, providing data-driven insights into water demand reduction and system performance. The simulation results indicate a 25 % reduction in freshwater demand due to the use of greywater in toilets and laundries, validated by continuous environmental monitoring and data analysis. These findings demonstrate that integrating water reuse infrastructure with real-time monitoring can significantly enhance water resource protection and provide a practical solution for sustainable water management in rural communities.